Cost of integrated immunization campaigns in Nigeria and Sierra Leone: bottom-up costing studies - Laura Boonstoppel; Flavia Moi; Christina Banks; Florence Sibeudu; Divine Obodoechi; Kyle Borces; Obinna Onwujekwe; Logan Brenzel (BMC, 2024)
Abstract Background To improve the efficient use of scarce resources, low- and middle-income countries and development partners are increasingly encouraged to deliver multiple vaccines and other interventions in a single integrated campaign. However, little is known regarding the cost of delivering vaccines through integrated campaigns, and the extent to which efficiencies are achieved. To fill this evidence gap, we estimated the cost of integrated immunization campaigns in Nigeria and Sierra Leone, and the potential savings from integration. Methods We conducted a retrospective ingredients-based costing study from a payer perspective of a campaign held in 2019 in Sierra Leone with measles-rubella vaccine and oral polio vaccine, during which nutrition supplements were also offered in part of the country, and yellow fever campaigns held in three states in Nigeria in 2019 and 2020, where in one state (Anambra) meningococcal A vaccines were co-delivered. We collected data from 108 health facilities, all relevant administrative levels, and implementing partners. We estimated the full financial and economic cost of each campaign, the average unit cost of delivery, as well as the cost by activity and resource type. We also estimated the cost savings from integration in Anambra state by modelling out the cost of the alternative of two standalone campaigns. Results The average financial delivery cost was $0.34 per dose in Sierra Leone, and the economic cost was $0.73 per dose. In Nigeria, the financial cost per dose was $0.29-$0.35 across the three states, and the economic cost per dose was $0.62-$0.85. Facilities and wards delivering more doses achieved a lower financial and economic unit cost of delivery, demonstrating evidence of economies of scale. We estimated that Anambra may have saved at least $1,204,133 in financial resources by integrating yellow fever and meningitis A vaccine delivery, amounting to $0.17 per dose delivered. When including opportunity costs, the economic cost saving was estimated at $0.34 per dose delivered. Conclusions The study offers evidence on what it costs to deliver integrated campaigns, and shows that integrated delivery is likely to result in significant cost savings. Where high delivery volumes can be achieved, integrated campaigns can benefit from economies of scale. The findings can be used to inform planning and budgeting for immunization campaigns in low- and middle-income countries.